Hubungan Motivasi Belajar Terhadap Hasil Belajar pada Mata Kuliah Teknik Laboratorium Mahasiswa Jurusan Pendidikan Biologi Angkatan 2021-2023 - Wani, Iin Hijrah; Hamansah, Hamansah; Rivai, Andi Tenri Ola (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the relationship between learning motivation and learning outcomes in the laboratory engineering course for biology education students in the 2021-2023 intake. This study is a quantitative correlational study. The subjects were 93 biology education students in the 2021-2023 intake. Data collection techniques used included questionnaires and documentation. The data analysis technique used is qualitative data analysis, which consists of data reduction, data presentation, and conclusion drawing. The results showed a high level of learning motivation and varying learning outcomes. The results showed a weak and insignificant relationship between the level of learning motivation and learning outcomes in the Laboratory Engineering course for biology education students in the 2021-2023 intake. Evidence from this study is shown by the Spearman correlation coefficient of r = 0.154, which indicates a very weak positive relationship, and a significance value of p = 0.139, which clearly exceeds the 0.05 significance limit. Therefore, it can be concluded that learning motivation does not have a direct influence on student learning outcomes in the context of this study.